Synthesis, crystal structures, spectral studies and reactivity of square planar copper(II) complexes containing Schiff base ligand - Pattanayak, Poulami
The reactions of HL1 [2-((2-(benzylthio)phenylimino)methyl)phenol] and HL2 [3-((2-(benzylthio)phenylimino)methyl)-2-hydroxy-5-methylbenzaldehyde] separately with Cu(OAc)2 center dot H2O afforded new Cu(II) complexes [Cu(L1)(OAc)] (1) and [Cu(L2)2] (2), respectively. These are characterized by microanalytical data and spectroscopic studies. UVvis spectra of the complexes show intense low-energy transitions approximate to 420nm which are ligand to metal charge transfer (LMCT) transitions. The single-crystal X-ray structures were determined for 1 and 2. Reactions of [Cu(L1)(OAc)] (1) with , SCN and show the replacement of weakly coordinated acetate yielding [Cu(L1)(N3)], [Cu(L1)(SCN)] and [Cu(L1)(NO2)], respectively. Unequivocal characterization of the substituted products has been done by single-crystal X-ray study of [Cu(L1)(N3)]. HL2 and its Cu(II) complex exhibited low-intensity emission bands at approximate to 575nm upon excitation at 375nm and at 420nm, respectively. Redox properties of the complexes were determined electrochemically. Density functional theory (DFT) computations have been carried out to explain the spectroscopic and redox properties of the complexes.